Enhancing one-year mortality prediction in STEMI patients post-PCI: an interpretable machine learning model with risk stratification - Li, Wenqiang; Yan, Dongdong; Hu, Wei; Su, Xiaoling; Zhang, Zheng (Frontiers in Artificial Intelligence, 2025)
BackgroundST-elevation myocardial infarction (STEMI) poses a significant threat to global mortality and disability. Advances in percutaneous coronary intervention (PCI) have reduced in-hospital mortality, highlighting the importance of post-discharge management. Machine learning (ML) models have shown promise in predicting adverse clinical outcomes. However, a systematic approach that combines high predictive accuracy with model simplicity is still lacking.MethodsThis retrospective study applied three data processing and ML algorithms to address class imbalance and support model development. ML models were trained to predict one-year mortality in STEMI patients post-PCI, with performance evaluated using accuracy, sensitivity, precision, F1-score, area under the receiver operating characteristic curve (AUROC), and the area under the precision-recall curve (AUPRC).ResultsWe analyzed data from 1,274 patients, incorporating 46 clinical and laboratory features. Using the Random Forest (RF) algorithm, we achieved an AUROC of 0.94 (95% confidence interval (CI): 0.90–0.98), an AUPRC of 0.44 (95% CI:0.15–0.76) in the internal validation set, identifying five key predictors: cardiogenic shock, creatinine, NT-proBNP, diastolic blood pressure, and left ventricular ejection fraction. By integrating risk stratification, the model’s performance improved, achieving an AUROC of 0.97 (95% CI: 0.96–0.99) and an AUPRC of 0.74 (95% CI: 0.60–0.84).ConclusionThis study highlights the feasibility of constructing accurate and interpretable ML models using a minimal set of predictors, supplemented by risk stratification, to improve long-term outcome prediction in STEMI patients.